HYDROGEOLOGICAL RESEARCH OF CONSUMPTION AND POLLUTION OF UNDERGROUND WATER - Radjabova , Mahliyo Makhmudovna; Ergashev , Mirsharif G‘anijon ugli (Educational Research in Universal Sciences, 2023)
In this article, recommendations are given on the existing irrigated areas in the Republic of Uzbekistan, their distribution by the level of salinity, as well as practical measures to prevent secondary salinity in the irrigated areas of Bukhara region. In the final part of the article, recommendations were given to land users on the effective use of irrigated areas in farming, methods for increasing the yield of agricultural crops.